Trajectories of Big Five Personality Traits: A Coordinated Analysis of 16 Longitudinal Samples. Issue 3 (5th May 2020) - Graham, Eileen K.; Weston, Sara J.; Gerstorf, Denis; Yoneda, Tomiko B.; Booth, Tom; Beam, Christopher R.; Petkus, Andrew J.; Drewelies, Johanna; Hall, Andrew N.; Bastarache, Emily D.; Estabrook, Ryne; Katz, Mindy J.; et al.
Abstract: This study assessed change in self‐reported Big Five personality traits. We conducted a coordinated integrative data analysis using data from 16 longitudinal samples, comprising a total sample of over 60 000 participants. We coordinated models across multiple datasets and fit identical multi‐level growth models to assess and compare the extent of trait change over time. Quadratic change was assessed in a subset of samples with four or more measurement occasions. Across studies, the linear trajectory models revealed declines in conscientiousness, extraversion, and openness. Non‐linear models suggested late‐life increases in neuroticism. Meta‐analytic summaries indicated that the fixed effects of personality change are somewhat heterogeneous and that the variability in trait change is partially explained by sample age, country of origin, and personality measurement method. We also found mixed evidence for predictors of change, specifically for sex and baseline age. This study demonstrates the importance of coordinated conceptual replications for accelerating the accumulation of robust and reliable findings in the lifespan developmental psychological sciences. © 2020 European Association of Personality Psychology